E-072 Use of eptifibatide as an alternative to preoperative standard dual antiplatelet therapy load for pipeline intracranial aneurysm flow diversion. (23rd July 2017) - Khan,; Ryan, R; Choulakian, A
Abstract : Introduction: Intracranial aneurysm flow diversion using the Pipeline Embolization Device (PED) has become a common mode of aneurysm treatment. Standard practice involves preoperative loading of a dual antiplatelet (DUAP) regimen that most commonly consists of clopidogrel and aspirin to prevent flow diverter thrombosis. However, preoperative dual antiplatelet treatment can exacerbate procedural hemorrhagic complications, since these agents cannot be easily reversed. By contrast, the antiplatelet effect of the glycoprotein IIb/IIIa agent eptifibatide wears off within 4 to 8 hours following discontinuation. We report the use of eptifibatide in a consecutive series of patients who underwent PED as an alternative to standard DUAP preoperative loading. Methods: All patients received an eptifibatide weight-based loading dose of 180 microgram per kilogram upon initial placement of the Pipeline device, with a 12-hour infusion of eptifibatide following completion of the bolus dose at a rate of 2 micrograms/kilogram/minute. All patients were loaded with clopidogrel and aspirin following postoperative clinical assessment, and prior to discontinuation of the eptifibatide 12-hour infusion. Clopidogrel and aspirin platelet inhibition was measured following discharge at least 10 days after discontinuation of epitifibatide to assure therapeutic platelet inhibition: the 10 day delay was utilized to avoid spurious platelet function results from residual traces of serum eptifibatide. Results: Seven consecutive patients underwent elective Pipeline flow diversion of unruptured intracranial aneurysms between October 2016 and February 2017. There were six women and one man in this cohort, with ages ranging from 33 to 61 with an average age of 51. All treated aneurysms were located in the intracranial anterior circulation. In one patient, endosaccular aneurysm coil placement was performed along with PED. All patients received a single Pipeline device except for one patient who received two telescoped Pipeline devices. There were no procedural complications in any of the seven PED cases. All patients were discharged home on postoperative day 1 with no evidence of new neurologic deficits or thromboembolic complications. Clopidogrel and aspirin platelet inhibition was measured for 4 of 7 patients two to three weeks after loading with clopidogrel and aspirin utilizing the Verify Now P2y12 and Aspirin Resistance Assay and were found to be therapeutic in all four patients. Conclusion: Eptifibatide administration is a safe and effective alternative antiplatelet strategy to preoperative dual antiplatelet loading with clopidogrel and aspirin prior to intracranial aneurysm Pipeline flow diversion. Disclosures: A. Khan: None. R. Ryan: 2; C; Penumbra, Inc. A. Choulakian: None.